2018
DOI: 10.1007/s10120-018-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

First-line chemotherapy with S-1 alone or S-1 plus cisplatin for elderly patients with advanced gastric cancer: a multicenter propensity score matched study

Abstract: Our findings do not support the survival benefit of SP over S-1 in elderly patients with AGC. We are now conducting a prospective comparative study to optimize treatment strategy and explore applicability of the geriatric assessment for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Two large retrospective studies demonstrated that CC was superior to SC in terms of OS [20, [20,21]. Moreover, because most randomized trials have included relatively young patients and patients with good PS, it is difficult to define the best chemotherapy strategy for elderly patients or those with poor PS [3][4][5][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two large retrospective studies demonstrated that CC was superior to SC in terms of OS [20, [20,21]. Moreover, because most randomized trials have included relatively young patients and patients with good PS, it is difficult to define the best chemotherapy strategy for elderly patients or those with poor PS [3][4][5][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Limited data are available regarding chemotherapy regimens for elderly patients with RPMGC, because such patients are underrepresented in clinical trials [3][4][5][8][9][10][11]. Two small retrospective studies comparing S-1 with S-1 and cisplatin (SP) for RPMGC patients older than 70 gave conflicting results, with both studies showing more severe toxicities in the SP group [11,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trial data that are available regarding the treatment of elderly patients with AGC is limited and is mostly derived from phase II studies conducted in elderly patients, age subgroup analyses of phase III studies, and retrospective analyses of elderly patient populations. Overall, evidence from these clinical trials suggests that chemotherapy is feasible in elderly patients with AGC [14,[24][25][26][27][28], but elderly patients with AGC are less likely to receive multiple lines of chemotherapy than younger patients [14,15]. For example, studies of first-line chemotherapy in elderly vs younger patients have reported rates of second-line chemotherapy of 38.7% vs 62.7% [14] and 24% vs 68% [15].…”
Section: Clinical Trial Datamentioning
confidence: 99%